The Effect of Intellectual Capital and Asset Management on Financial Performance - Leny Suzan; Marsheli Indira Putri (UNIVERSITAS PAKUAN, 2023)
One of the industries that can expand quickly in Indonesia is the food and beverage sector. This study aims to identify the impact of asset management and intellectual capital on financial performance. The population of this study is Food and Beverage Subsector companies listed on the Indonesia Stock Exchange during 2018 to 2021. This study used the purposive sampling method so that 19 companies were obtained for four consecutive years. The data was tested by using the panel data regression analysis method. The independent variables of this study are Intellectual Capital proxied with VAIC and Asset Management proxied with TATO. ROA is used in this study as a proxy for financial performance, the dependent variable. This study demonstrates how intellectual capital affects financial performance favorably. In the meantime, asset management has no significant impact on financial performance.